Characteristics of Methicillin-Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA) and their inhibitory response by ethanol extract of Abrus precatorius - BQ. MUTMAINNAH; AFAF BAKTIR; NI’MATUZAHROH NI’MATUZAHROH (Society for Indonesian Biodiversity, 2020)
Abstract. Mutmainnah BQ, Baktir A, Ni’matuzahroh. 2020. Characteristics of Methicillin-Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA) and their inhibitory response by ethanol extract of Abrus precatorius. Biodiversitas 21: 4076-4085. Three isolates of Staphylococcus bacteria with the code MRSA 22372, MSSA 22187 and MSSA 22366 originated from the urine of the patient at Dr. Regional General Hospital Soetomo, Clinical Microbiology Installation Surabaya, Indonesia. Differences in bacterial strains affect their sensitivity to antimicrobial agents. The active ingredient of the ethanol extract of the leaves of Abrus precatorius L. has the potential to inhibit bacterial growth. This study aims to further characterize the bacteria MRSA 22372, MSSA 22187 and MSSA 22366 based on morphological, biochemical and molecular characters and to compare the growth inhibitory response of these three bacteria due to the treatment of variations in the ethanol extract of A. precatorius of 25 mgL-1- 800 mgL-1 leaves. The results showed there were differences in the diameter of bacterial colonies, the ability to ferment glucose and sucrose, and the production of urease and catalase. The molecular characteristics of the three bacteria have no similarity in the order of nucleotide bases or phylogenetic proximity to each other. Ethanol extract of A. precatorius leaves at a concentration of 800 mgL-1 inhibited the growth of MSSA 22187 with an inhibition zone of 41 mm and decreased the MSSA 22366 growth by 67.6%. MIC value of ethanol extract of A. precatorius leaves in all three bacteria was 25 mgL-1 with growth inhibition up to 29.4%, 35.3%, and 29.4% respectively. Keyword : MRSA, MSSA, ethanol extract, Abrus precatorius L.